Moderating Role of Gender in the Influence of Peer Pressure on Adolescents’ Sexual Adventurism in Ghana - EYIAH-BEDIAKO, Sylvia; OMOTOSHO, Joshua Adebisi; FIA, Stephen Doh; BENTIL, Josephine Anterkyi; BOYE, Joy Olive; DABONE, Kyeremeh Tawiah (Ilorin Journal of Education, 2025)
The rationale behind this study was to assess the moderating role that gender plays in the influence of peer pressure on adolescents’ sexual adventurism in Ghana. A total of 525 adolescents whose ages range between 12 and 19 in junior high schools were selected using the multistage sampling approach. The Youth Sexual Intention Questionnaire (YSI-Q) and the Peer Pressure Scale (PPS) were used for data collection. The data were statistically analysed using standard deviation, mean, multiple regression, multivariate linear regression, simple moderation analysis and three-way interaction moderation analysis. The results revealed that the level of peer pressure and sexual adventurism was high among the respondents. Peer pressure and gender significantly and independently predicted sexual adventurism. Gender served as a significant moderator in the relationship between peer pressure and sexual adventurism. Based on the findings, it was recommended that teachers and parents provide educative platform at school, home and the media in order to inform adolescents on peer pressure and sexual issues.